Cyberbullying Behavior of Junior High School Students in Demonstration School of Phranakhon Si Ayutthaya Rajabhat University - Hanvilai , Chayanit; Hombunma , Pannathorn (Journal of Dhamma for Life, 2025)
The purposes of this research were to: 1) to study level of cyberbullying behavior of junior high school students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University; 2) compare the cyberbullying behavior of junior high school students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University classified by their personal factors; and 3) provides guidelines for cyberbullying behavior of junior high school students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University. The sample group, obtained by stratified random sampling, consisted of 210 Students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University. The research instrument was a questionnaire of cyberbullying behavior of junior high school students in demonstration school of Phranakhon Si Ayutthaya Rajabhat University with a reliability level at 0.92. Statistical analysis was performed in terms of frequency, percentage, mean, standard deviation, t-test, one-way ANOVA, LSD test, The research findings revealed as follows: 1) cyberbullying behavior of lower secondary school students in the Demonstration School of Phranakhon Si Ayutthaya Rajabhat University was at a moderate level overall. The aspect with the highest average value was gossiping or cursing others, followed by deleting or blocking others, and the aspect with the lowest average value was impersonating others in a negative way; 2) students with different genders, ages, grade levels, latest academic results, average family income, marital status of father and mother, father's occupation, and mother's occupation have similar opinions on cyberbullying behavior overall; and 3) Guidelines for reducing cyberbullying behavior: gossiping or cursing others, there are 16 items, such as do not post gossip or curse others in cyberspace because it is a bad thing; defamation of others, there are 11 items, such as do not post defamation of others in cyberspace; and impersonation of others in a negative way, there are 11 items, such as having a good conscience and not impersonating others in a negative way. Think about empathy and the impact it will have on others. In terms of disclosing personal or other people's secrets, there are 9 items, such as parents, guardians, or teachers should teach children that they should not disclose their own personal information on cyberspace. And in terms of deleting or blocking others, there are 6 items, such as deleting or blocking others if it is a personal matter, it is an individual's right to do so. But if it is a group with a large number of people using it together, deleting or blocking others without reason should not be done.